Efektifitas Penggunaan Media Pembelajaran (Pada Mata Pelajaran Pendidikan Agama Islam) (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
In order to make teaching and learning can take place with good and perfect is influenced by a variety of important factors supporting them are media education, media as a carrier of information between a source and a receiver information. Learning media use has a very important meaning, in addition to complement and enrich the teaching materials, as well as being a medium of learning that can enhance creativity and effectiveness in student learning. In general the media teaching religious education have three forms, namely media viewpoint (visual aids ), the media listen (audio aids) and the media heard-of view of (audio-visual aids). Learning media use at the stage orientation will help greatly the effectiveness of the learning process and the delivery of the message and the content at that time. In this case there are several factors that influence the effective learning of religious education in schools, including; teachers, students, facilities and infrastructure, the purpose of education and curriculum. In the implementation of the learning process of teachers suffered obstacles, namely the lack of props so troublesome in the delivery of the material, the book packages that are not complete and still the presence of students who are less able to understand the learning material using media and very few hours of instruction